Spontaneous and environment induced genomic alterations in yeast model - Ke-Jing Li; Lei Qi; Ying-Xuan Zhu; Min He; Qian Xiang; Dao-Qiong Zheng (Cell Insight)
While genomic alterations are fundamental to biological evolution, enabling adaptation and diversity, they can also result in detrimental outcomes, such as the development of genetic diseases including cancer. The budding yeast Saccharomyces cerevisiae serves as an exemplary model for investigating the mechanisms behind various genomic alterations, including point mutations, chromosomal rearrangements, and whole-chromosome aneuploidy. In this review, we highlight the application of genetic screening systems to assess the mutagenic effects of physical and chemical agents efficiently. Additionally, we discuss the utilization of high-throughput sequencing technologies to uncover comprehensive genomic alterations and rare genetic events. We provide a detailed summary of the features of genomic alterations and discuss the genetic mechanisms driving these changes under both spontaneous and stress-induced conditions. Given the high conservation of DNA replication and repair machinery across different organisms, the insights gained from studies on yeast offer valuable perspectives for understanding the delicate balance between genome plasticity and integrity in other species.